GURU KREATIF DALAM PENGEMBANGAN MEDIA PEMBELAJARAN IPS DI MI MA’ARIF NU 01 BUNGKANEL - Rodiyatun; Tutuk Ningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe teachers’ creativity in developing social studies learning media at MI Ma’arif NU 01 Bungkanel and to analyze its impact on students’ learning processes and outcomes. The research employed a qualitative approach with a descriptive method. Data were collected through observation, in-depth interviews, and documentation, involving social studies teachers, the principal, and students as research subjects. The findings reveal that teachers are able to develop creative learning media despite limited facilities. Teachers utilized simple media such as hand-drawn maps, real objects, village miniatures, and buying selling simulations to present social studies material in a more concrete and engaging way. This creativity significantly enhanced students’ motivation, engagement, and comprehension of the subject matter. Moreover, the principal’s support and a conducive school culture encouraged teachers to continuously innovate. These findings are consistent with Edgar Dale’s Cone of Experience, Piaget’s constructivism, Dewey’s learning by doing, and Bloom’s taxonomy of learning domains. The study concludes that teachers’ creativity in developing learning media is a key factor in creating active, interactive, and meaningful social studies learning for elementary madrasah students. Keywords: Creative teacher, learning media, social studies, MI Ma’arif NU 01 Bungkanel